How to start insulin treatment: Earlier or delayed insulin therapy - (:unkn) unknown (ELSEVIER IRELAND LTD, 2006)
No consensus exists as to the best time for starting insulin treatment in patients with type 2 diabetes. Glucose toxicity is a significant factor which affects the approach to treatment at various stages of the disease. Those who advocate early insulin use cite studies which have used CSII or intensive insulin therapy in newly-diagnosed type 2 diabetics and have achieved long-term glycemic control without medication, similar to the honeymoon in type 1 diabetic patients. Although there are studies showing improved control with maximal dose sulfonylurea. therapy, glucose control takes longer to achieve and HbA1c levels remain higher than current targets. It is evident that without insulin, our patients will perpetually remain below target and suffer the consequences of hyperglycaemia, even if mild. (c) 2006 Published by Elsevier Ireland Ltd.
Keywords: early insulin treatment; type 2 diabetes mellitus; glucotoxicity; diabetic complications; TYPE-2 DIABETIC-PATIENTS; TERM GLYCEMIC CONTROL; PANCREATIC-ISLETS; INDUCTION; SECRETION; MORTALITY